ANTESENDEN AFFECTIVE COMMITMENT PADA KARYAWAN HOTEL BINTANG TIGA DI CIPANAS - Nita Erfiyani; Dita Oki Berlyanti; Wiwik Robiatul Adawiyah (Business, Economics dan Entrepreneurship, 2023)
This study aims to analyze the influence of Morality, Employee Engagement onAffective Commitment. The sampling method used was purposive sampling with 86 employees of three star hotel in Cipanas, Sangga Buana. The data analysis technique in this study used a test technique instrument using multiple linear regression. The results of this study indicate that Morality and Employee Engagement have a positive effect on Affective Commitment. The managerial implications of this research are in organizations apply Morality, so that employees are comfortable at work.